Trends in Cross-Border Funding - Gähwiler, Barbara; Nègre, Alice (Washington, DC: World Bank, 2012)
Microfinance funding is becoming more transparent. More than 60 microfinance funders regularly report information on their microfinance portfolio to Consultative Group to Assist the Poorest (CGAP), and extensive data are available on microfinance investment vehicles (MIVs) through symbiotic and micro-rate. In 2011, CGAP surveyed the 20 largest microfinance funders, which represented over 85 percent of commitments reported in the previous survey year. Based on the findings of that survey and previous surveys, this brief describes global trends in microfinance funding between 2007 and 2010.